Progression of aortic stenosis in patients with bicuspid aortic valve. Issue 12 (28th September 2021) - Shang, Michael; Kahler‐Quesada, Arianna; Mori, Makoto; Yousef, Sameh; Geirsson, Arnar; Vallabhajosyula, Prashanth
Abstract: Background: Bicuspid aortic valve is the most common congenital heart defect and predisposes patients to developing aortic stenosis more frequently and at a younger age than the general population. However, the influence of bicuspid aortic valve on the rate of progression of aortic stenosis remains unclear. Methods: In 236 patients (177 tricuspid aortic valve and 59 bicuspid aortic valve) matched by initial severity of mild or moderate aortic stenosis, we retrospectively analyzed baseline echocardiogram at diagnosis with latest available follow‐up echocardiogram. Baseline comorbidities, annualized progression rate of hemodynamic parameters, and hazard of aortic valve replacement were compared between valve phenotypes. Results: Median echocardiographic follow‐up was 2.6 (interquartile range [IQR] 1.6–4.2) years. Patients with tricuspid aortic stenosis were significantly older with more frequent comorbid hypertension and congestive heart failure. Median annualized progression rate of mean gradient was 2.3 (IQR 0.6–5.0) mmHg/year versus 1.5 (IQR 0.5–4.1) mmHg/year ( p = .5), and that of peak velocity was 0.14 (IQR 0–0.31) m/s/year versus 0.10 (IQR 0.04–0.26) m/s/year ( p = .7) for tricuspid versus bicuspid aortic valve, respectively. On multivariate analyses, bicuspid aortic valve was not significantly associated with more rapid progression of aortic stenosis. In a stepwise Cox proportional hazards model adjusted for baseline mean gradient, bicuspid aortic valve was associated with increased hazard of aortic valve replacement (hazard ratio: 1.7, 95% confidence interval [1.0–3.0], p = .049). Conclusion: Bicuspid aortic valve may not significantly predispose patients to more rapid progression of mild or moderate aortic stenosis. Guidelines for echocardiographic surveillance of aortic stenosis need not be influenced by valve phenotype.